Signaling by cellular protrusions: keeping the conversation private - Buszczak, Michael (Trends Cell Biol, 2016)
Information exchange between different cells makes multicellular life possible. Signaling between cells can occur over long distances, as in the case of hormone signaling, or it can take place over short distances between immediately juxtaposed neighbors, as in the case of stem cell-niche signaling. The ability of signal-sending and –receiving cells to communicate with one another in a specific manner is of paramount importance in the proper development and function of tissues. Growing evidence indicates that different cellular protrusions help to achieve specificity in signaling that occurs between distinct cell types. Here, we focus on new roles for cellular protrusions in cell-to-cell communication, drawing special attention to how stem cells use specialized extensions to promote reception of self-renewing signals emanating from the niche.